Comparative Study of Outcome of two Methods (Sutures Vs Staples) of Skin Closure in Orthopedic Surgery - Gohiya, Ashish; Chandra Gupta, Dinesh; Gaur, Sanjiv (International Journal of Medical Research and Review, 2015)
Introduction: Surgical site wound closure plays a vital role in post-operative success. The use of either sutures or staples for skin approximation is a vital and frequently debated issue. We compared the outcome, using staples versus sutures, in open elective orthopedic surgical procedures. Material and Methods: This study was done over a period of 2 years at Department of Orthopedics Gandhi Medical College Bhopal. Patients aged between 18 to 80 years undergoing elective open surgeries were included. Computer generated random number randomized them in two groups. Skin closure was done by either monofilament nylon or metallic staples. The wounds were assessed in terms of discharge and if discharge showed bacterial growth than it was considered as wound infection. Wound dehiscence, pain during removal on the basis of VAS pain scale was also noted. Follow up was done in the 6th week in terms of patient satisfaction using visual analogue scale (VAS) and validated cosmesis scoring system Hollander Wound Evaluation Score (HWES). Results : Total 503 wounds were included in this study (262 in suture and 241 in staple groups), 14 (5.3%) wounds were culture positive in the suture group within 8th postoperative day as compared to 36(14.9%) in staples group with χ2 9.65 and (p=0.002) which is significant. 320 wounds with >10cms incision were analyzed (166 in suture and 154 in staple group) out of which 12 (7.22%) were infected in suture group and 24 (15.5%) in staple group with χ2 was 7.6 and (p=0.006) that statistically significant. Conclusion: We found a statistically significant higher incidence of superficial wound infection following skin closure by metallic staples as compared to monofilament nylon. This incidence of wound infection is detrimental to patient safety and also increases hospital stay and cost.